THE CORRELATION BETWEEN TROPONIN I LEVEL WITH CORRECTED THROMBOLYSIS IN MYOCARDIAL INFARCTION FRAME COUNT IN PATIENTS WHOSE UNDERWENT PRIMARY PERCUTANEOUS CORONARY INTERVENTION: A SINGLE CENTER STUDY - SYAFRI, MASRUL; DARWIN, ERYATI; YERIZEL, ETI; HARDISMAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: There were studies reported about the correlation between troponin I with scale of myocardial infarction (MI) area. However, the effect of revascularization into the coronary flow has not been reported. We aim to determine the correlation between high sensitivity troponin I and the successfulness of revascularization primary percutaneous coronary intervention (PPCI) in ST-elevation MI (STEMI) patients. The successfulness of revascularization was assessed by calculating Corrected thrombolysis in MI frame count (CTFC). Methods: This is a retrospective analysis including all consecutive patients undergoing PPCI over 1-year period from December 2018 to 2019 at the Integrated Heart Service Installation Dr. M. Djamil Padang Hospital, West Sumatra. Exclusion criteria included patients with incomplete medical record data, incomplete coronary angiography data, prior MI, and prior PCI and coronary artery bypass graft. Patients were put into two groups with normal (CTFC <30) and high (CTFC ≥30) to define the baseline characteristics. Results: A retrospective analysis was performed of patients undergoing primary PCI. Ninety-six patients underwent PPCI between December 2018 and 2019 were enrolled. For the baseline characteristic, patient was divided into two groups with normal CTFC (<30) and high (CTFC ≥30). There was negative weak correlation between troponin I level and CTFC with Spearman’s correlation value was 0.371 and correlation coefficient −0.092. Conclusion: Troponin I level at first presentation before revascularization did not have a significant correlation with coronary flow result after revascularization in STEMI patients.